Code Switching in “Just Alvin” Talk Show Program on Metro TV - Ade Rahmah Nasution; Rahmad Husein (LINGUISTIK TERAPAN, 2016)
The objectives of the study are to find out the types of code switching occurring in the talk show, the process of code switching, and the reasons for code switching in the talk show. This research was conducted by qualitative content analysis method. The data were obtained from the downloaded videos and then were transcribed. The data were four episodes of Just Alvin talk show. The transcriptions were analyzed by applying qualitative method. The findings showed that all types of code switching, i.e. lexical, phrasal, clausal code switching, idiomatic code switching and proverbial code switching occurred in all episodes. The realization of code switching in the talk show by inserting a word or terms of English language and alternating the language in the form of idiom or proverb. The reasons for code switching were found, such as; (1) Avoiding candid talk about something sensitive and private, (2) Selecting the audience and protecting from negative opinion, (3) Avoiding candid talk about something embarrassing in our country. It is concluded that the different topic and context create different criteria too as reasons of someone switch their language.   Keywords: achievement,code-switching, personal life